PENINGKATAN KEANDALAN PENYULANG TUKAD MUSI DAN PENYULANG BATANGHARI PT.PLN (PERSERO) UP3 BALI SELATAN ULP SANUR DENGAN POLA RADIAL - Nyoman Ananda Tri Utami; I Gede Dyana Arjana; I Wayan Sukerayasa (Jurnal SPEKTRUM, 2023)
The reliability of the distribution system will affect the quality of the electrical energy received by customers. The system will be said to be reliable if the disturbances and power outages that occur for a certain period of time are below the index set by an institution. The measure of the reliability of a system can be measured through the value of SAIDI (System Average Interruption Duration Index) or how long the system is interrupted and SAIFI (System Average Interruption Frequency Index) or how often a system is interrupted within 1 year and it was found that SAIFI's Tukad Musi Feeders were 1.9255 interruptions/subscribers per year, SAIDI were 26.5966 hours/customers per year and SAIFI's Batanghari Feeders were 1.6992 interruptions/subscribers per year, and SAIDI were 18.1486 hours/ subscribers per year by adding a component in the form of LBS to the two feeders will increase the reliability of the Tukad Musi feeder SAIFI of 1.8855 interruptions/customer per year, SAIDI of 26.0606 hours/customer per year and of Batanghari SAIFI feeder of 1.6814 interruptions/subscriber per year, SAIDI of 15.7925 hours / customer per year.